2012
DOI: 10.1007/s10620-012-2461-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement Measures Lead to Higher Surveillance Rates for Hepatocellular Carcinoma in Patients with Cirrhosis

Abstract: Implementation of QI measures incorporating automatic reminders of surveillance status for providers can significantly increase the rate of HCC surveillance among cirrhosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…43 Prior studies confirm these reported interventional study results though others have not had as much success highlighting the need for more research into the complex and dynamic concept of adherence. 34,35,[44][45][46] This study has several limitations. There was very large heterogeneity among included studies.…”
Section: Discussionmentioning
confidence: 96%
“…43 Prior studies confirm these reported interventional study results though others have not had as much success highlighting the need for more research into the complex and dynamic concept of adherence. 34,35,[44][45][46] This study has several limitations. There was very large heterogeneity among included studies.…”
Section: Discussionmentioning
confidence: 96%
“…Our study builds upon our prior results demonstrating the benefits of a structured surveillance program. (23) Our program using electronic medical record reminders achieved consistent HCC surveillance every 6 months in 46% of enrolled cirrhosis patients over a median of 2.2 years. Furthermore, most patients without consistent surveillance only missed 1 or 2 surveillance examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies assessing chronic disease management programs, including nursing-based protocols and automated reminders, demonstrated increased one-time HCC screening rates from 74% and 89% at baseline to 93% and 100%, respectively. 27, 28 However, both studies were conducted among patients followed by hepatologists and required patient consent, introducing a selection bias. In a subsequent quasi-experimental study, point-of-care clinical reminders targeting primary care providers increased screening rates from 18.2% to 27.6% (p<0.001); 29 however, intervention benefit was limited to patients with documented cirrhosis and those engaged in clinic.…”
Section: Discussionmentioning
confidence: 99%